Building social commmunities around alternate reality games - Petridis, Panagiotis; Dunwell, Ian; Arnab, Sylvester; Scarle, Simon; Qureshi, Adam; De Freitas, Sara; Protopsaltis, Aristidis; Star, Kam (Proceedings - 2011 3rd International Conferenceon Games and Virtual Worlds for Serious Applications, VS-Games 2011, 2011)
In recent years, alternate reality games have entered the mainstream as a new form of entertainment. The Living Stories project is the first alternate reality game in the UK, which addresses environmental issues. Living Stories combines social networking sites such as Facebook and Twitter with Second Life, to create a platform, which allows social networking to feed into content creation within a virtual world, and facilitate and encourage real-world behaviour through virtual rewards. The project is funded by Interactive Digital Media IDM, as part of an ongoing collaboration with the Eden Project, Coventry University Serious Games Institute and PlayGen Ltd. The aim of this project is twofold: firstly to engage new visitors and to extend the Eden experience beyond the actual visits, and secondly to increase user participation amongst groups that do not traditionally visit Eden Project. In this paper we describe the unique technical and pedagogic challenges addressed when creating this platform and consider how the state-of-the-art in alternate reality gaming can be applied in an educational ('serious') context. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: Alternate reality; Mixed reality; Serious games